Pengaruh Arah Irisan dan Tingkat Ketebalan Irisan Jahe terhadap Tingkat Kehalusan Tepung Jahe - Afrilia, Yuliani; Tamrin, Tamrin; Amien, Elhamida Rezkia; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
Ginger has a fairly high fiber content that can affect the flour produced when it goes through the powdering process. The purpose of this research was to determine the effect of the direction and the thickness of ginger slices on the level of flour fineness. The experiment was conducted by using a completely randomized design (CRD) with two factors. The first factor is the direction of the slice with two treatments, namely vertical slice (V) and horizontal slice (H). The second factor was the thickness of the slices with three levels, namely 2 mm (T1), 4 mm (T2), and 6 mm (T3). It treatment combination was carried out in triplicates. The parameters observed were moisture content, repose angle, degree of fineness, uniformity index, grain yield, bulk density, and color. The data obtained were analyzed by using Anova test available in Excel and SAS, if there is significant different among the parameters, then is followed by LSD test at α = 0,05. The results showed that the direction of slices significantly affect the fineness of the flour, in which vertically sliced cuts produced better fineness than that of horizontally sliced cuts. The thickness of cuts did not significantly influence the flour characteristic. Keywords:  Fineness, Ginger, Ginger Fiber, Ginger Flour, Slice Direction, Thickness of the Slices.